Legal Analysis on Accountability for the Management of Evidence for Narcotics Crimes - Erwin Juliandi Sipakkar; Abdul Rahman Maulana Siregar; Syahranuddin Syahranuddin (Fakultas Hukum Dehasen, 2026)
The management of evidence in narcotics criminal cases is the most important stage in the criminal justice system because it is directly related to evidence and legal certainty. Inaccuracies in the administration, storage, and destruction of evidence have the potential to cause abuse of authority, loss of evidence, and even weaken the law enforcement process. This study aims to analyze the legal aspects of accountability for the management of evidence of narcotics crimes in the South Nias District Attorney's Office, identify the management mechanisms applied, and assess the obstacles that affect the effectiveness of its implementation. The research method used is empirical legal research with a legislative approach. Data was obtained through a literature study of regulations related to evidence management and interviews. The results of the study show that the management of evidence has been carried out according to administrative procedures, starting from receipt, recording, storage, to destruction, but obstacles are still found in the form of limited storage facilities, lack of human resources, and not optimal supervision. Legal accountability in the management of evidence is based on the principles of office accountability, administrative responsibility, and potential criminal liability in the event of irregularities. Therefore, it is necessary to strengthen the supervision system, digitize administration, and increase the capacity of the apparatus to ensure transparency and integrity in the management of evidence. This research is expected to make a conceptual and practical contribution in improving the professional and fair governance of narcotics evidence.